Solid waste landfill site selection using analytical hierarchy process (AHP): a case study in Kuantan, Pahang, Malaysia - Mohd Hazwan, Hamdan (2013)
Site selection is crucial and necessary for waste management in areaswh&éaregrowing rapidly. Due to the complexity of waste management systems to choose 'a neWlárdfihl as appropriate, a number of alternatives and evaluation criteria required for èonsidèration. A study was carried out in the Kuantan, Pahang to overcome the problem of.critical l capacity of waste disposal sites. The aims of this study are to determine the appropriate evaluation criteria for the selection of waste disposal site and to identify and rank the potential disposal site in Kuantan, Pahang. A multi criteria decision making technique, Analytical Hierarchy Process (AHP), which utilizes a multi-level hierarchy structure consist of objective, criteria, sub-criteria, and alternatives is applied in this study. The input from the experts has been used to determine the evaluation criteria. Eleven criteria has been selected and classified into four main categories, ...which-, are hydrologicallhydrogeological factor, morphologic, social criteria and economicimpact Three potential landfill sites had ibeen identified as alternatives, which are SungaiKaraiig, Tanjung Lumpur and Beserah. Athe result, Beserah had been ranked as thefirstaltematives with highest composite priorities values (0.390), followed by Tanjung Lumpur (0.323) and Sungai Karang (0.287).